Z-scheme CdS–Au–BiVO4 with enhanced photocatalytic activity for organic contaminant decomposition. Issue 1 (5th December 2016) - Bao, Shenyuan; Wu, Qiangfang; Chang, Shunzhou; Tian, Baozhu; Zhang, Jinlong
Abstract : A Z-scheme heterogeneous photocatalyst CdS–Au–BiVO4 was synthesized for the first time by photo-reduction and deposition–precipitation methods. Abstract : A Z-scheme heterogeneous photocatalyst CdS–Au–BiVO4 was synthesized for the first time by photo-reduction and deposition–precipitation methods. The microstructures and optical properties of the as-prepared samples were investigated by means of scanning electron microscopy (SEM), field emission scanning electron microscopy (FE-SEM), high resolution transmission electron microscopy (HR-TEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and UV-vis diffuse reflectance spectroscopy (DRS). Due to the oriented accumulation of electrons on the 010 facets of BiVO4 crystals, Au nanoparticles were successfully anchored on the 010 facets of BiVO4 crystals via the photo-reduction process. CdS was further selectively deposited on the surface of Au nanoparticles, benefitting from the strong S–Au interaction. Photocatalytic degradations of tetracycline and Rhodamine B indicated that CdS–Au–BiVO4 exhibits much higher photocatalytic activity than BiVO4, Au–BiVO4, and CdS–BiVO4 . Radical trapping experiments confirmed that in the case of CdS–Au–BiVO4, the main reactive species responsible for organic contaminant degradation are h +, ˙OH, and ˙O2 −, while only h + can be produced in the case of CdS–BiVO4 . Based on the photoelectrochemical analysis and radical trapping experiments, it can be deduced that the Z-scheme structure of CdS–Au–BiVO4 not only decreases the recombination rate of photo-generated carriers but also makes the holes and electrons keep a higher redox ability.